2000
DOI: 10.1152/ajpheart.2000.279.5.h2124
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic role for mitochondria in palmitate-induced cardiac myocyte apoptosis

Abstract: After cardiac ischemia, long-chain fatty acids, such as palmitate, increase in plasma and heart. Palmitate has previously been shown to cause apoptosis in cardiac myocytes. Cultured neonatal rat cardiac myocytes were studied to assess mitochondrial alterations during apoptosis. Phosphatidylserine translocation and caspase 3-like activity confirmed the apoptotic action of palmitate. Cytosolic cytochrome cwas detected at 8 h and plateaued at 12 h. The mitochondrial membrane potential (ΔΨ) in tetramethylrhodamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
144
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 53 publications
8
144
0
Order By: Relevance
“…However, because these inhibitors did not block apoptosis, we conclude that ceramide accumulation is not involved in palmitate-induced apoptosis. Recent data obtained with CHO cells and cardiomyocytes also support a non-essential role for de novo ceramide synthesis in palmitate-induced apoptosis (13,44). Excess palmitate may also lead to increased mitochondrial ␤-oxidation pathway generating ROS in excess of endogenous antioxidant.…”
Section: Discussionmentioning
confidence: 85%
“…However, because these inhibitors did not block apoptosis, we conclude that ceramide accumulation is not involved in palmitate-induced apoptosis. Recent data obtained with CHO cells and cardiomyocytes also support a non-essential role for de novo ceramide synthesis in palmitate-induced apoptosis (13,44). Excess palmitate may also lead to increased mitochondrial ␤-oxidation pathway generating ROS in excess of endogenous antioxidant.…”
Section: Discussionmentioning
confidence: 85%
“…The membrane-permeable dye DCFH-DA enters cardiomyocytes and produces a fluorescent signal after intracellular oxidation by ROS such as hydrogen peroxide and the hydroxyl radical (29). Neonatal cardiomyocytes were incubated in palmitate or the control fatty acid oleate for 4 or 20 h. We have previously shown that exposure of these cells to palmitate for 4 h is sufficient to induce mitochondrial cytochrome c release, whereas after 20 h, palmitate causes caspase-3-like activation, increased ceramide production, and DNA laddering (8,26). With the use of video microscopy of live cells and examination of multiple fields of cells, we were unable to detect any increase in fluorescence in palmitate-treated cells over control oleate-treated cells at either time.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that this apoptosis is characterized by an early mitochondrial release of cytochrome c and a loss of mitochondrial membrane potential (26). Later events include an increase in ceramide synthesis, inhibition of mitochondrial electron transport complex III, activa- Values are means of caspasase-3-like activity (in fluorescence units ⅐ min Ϫ1 ⅐ mg protein Ϫ1 ) Ϯ SE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations